Delayed Achilles tendon ruptures. Does non-operative management work? - Nicholas Owen (Proceedings of the 13th meeting of the combined orthopaedic associations, Cape Town, 2016, 2016)
Delayed Achilles tendon ruptures. Does non-operative management work?Authors: R.D. Macnair, AM Hutchison, R.M. Evans, N.J. Owen, C. Topliss, P.R.Williams Delayed Achilles tendon ruptures are difficult to manage, with surgical treatmentgenerally advised. The purpose of this study was to report the outcomes of patientswith a delayed presentation of an Achilles tendon rupture (2 weeks plus) treatedconservatively with a dedicated management programme.Methods. We identified all patients with a delayed presentation who had been treatedconservatively at our centre from 2008 – 2014. The conservative management wasthe same as for our acute Achilles ruptures: the Swansea Morriston Achilles RuptureTreatment (SMART protocol). This includes 1) an ultrasound examination followed byimmobilisation in a position which allowed the smallest gap between the tendon ends2) referral to a dedicated Achilles tendon clinic and 3) strict rehabilitation guidelines.Outcome measures included complication rates (re-rupture / venous thromboembolism);Achilles Tendon Total Rupture Score (ATRS) and Achilles Repair Score (ARS); andmuscle function dynamometry assessing plantarflexion torque of the ankle. MRI ofruptured and non-ruptured legs allowed measurement of Achilles tendon length.Comparisons between the two sides were made (2-tailed t-test).Results. 19 patients were assessed; 16 males, 3 females. The mean age was 60years (range 39-80). The mean delay from injury to starting treatment was 61 days(range 14-249) and the mean follow-up was 40 months (range 13-87). There wereno re-ruptures. One patient had a pulmonary embolus. One patient went on to surgery.The mean ATRS was 65/100 (17-100), and ARS 71/100 (30-100). The meanplantarflexion torque for the injured side was 19.5 newton metres (N.m) (6.3-34.2,SD 8.2) and for the uninjured side 25.7 N.m (12.2-43.3, SD 9.1). The differencebetween the two sides was significant (t = 3.816 p = 0.001). The mean length ofthe injured Achilles tendon was 104.9mm (51.4-155.2) and uninjured 97.306mm(42.9-138.7). No significant difference (t = 1.684, p= 0.111).Conclusion. This comprehensive review of a conservative management regime forpatients with a delayed presentation Achilles rupture using the dedicated SMARTrehabilitation programme supports a satisfactory outcome in the majority of cases.Proceedings of the 13th meeting of the combined orthopaedic associations, Cape Town, 2016